KEBIJAKAN PENDUKUNG UNTUK PENGEMBANGAN PENCAIRAN BATUBARA DI INDONESIA - Adhi Dharma Permana; Ira Fitriana; Ratna Etty Puspita Dewi (Badan Pengkajian dan Penerapan Teknologi, 2011)
From a technological perspective, coal liquefactiontechnology holds promise to provide synthetic liquid fuels as a substitute for conventional liquid fuels. The Indirect Coal to Liquid (CTL) approach using Fischer-Tropsch (FT) technology developed by SASOL has been commercially implemented in South Africa. On the other hand, the Direct CTL approach developed by Brown Coal Liquefaction (BCL) of Japan has not matured into a commercially proven technology. Applying coal liquefaction technology using low rank coal inIndonesia will be a strategic effort to reduce dependence on conventional fuels. It is projected that domestic fuels consumption in the future will be met mostly by imported fuels. The main constraints in applying coal liquefaction technology are due to the high investment costs, the sensitivity of fuels from CTLtechnology to oil price which affects their market competition, and assurance of coal supply and requirement for processing synthetic fuels product from the CTLplant into final products. This paper describes the policy measures to support implementing CTL technology in Indonesia..Kata kunci: coal liquefaction, coal to liquid, policy strategy